Postmyocardial syndrome after myocardial infarction and percutaneous coronary intervention - A. A. Klimenko; N. A. Demidova; V. V. Veselkin; T. A. Kirdyashkina; A. A. Chinova; Yu. A. Shandanovina (Рациональная фармакотерапия в кардиологии)
Postmyocardial syndrome (Dressler syndrome) is a form of secondary pericarditis with or without pericardial effusion resulting from myocardial damage. Dressler syndrome is not a common disease, but it should be suspected in patients with pathognomonic symptoms after a myocardial infarction (MI). The article presents a clinical case of a 65-year-old man, a smoker who is overweight, with a history of hypertension, MI with ST segment elevation, stenting of the envelope branch of the left coronary artery, thrombospiration. According to coronary angiography, the patient revealed a multivessel lesion of the coronary arteries. Two weeks after stenting, the patient’s condition worsened: shortness of breath, pain in the left half of the chest, fever appeared. During the examination at the outpatient stage, bilateral hydrothorax and hydropericardium were revealed. He was hospitalized, was treated with ibuprofen 600 mg 3 times a day for 7 days, with a positive effect. Ten days after discharge, the patient noted an increase in shortness of breath, an increase in body temperature, a recurrence of dull chest pain. He was hospitalized at the Vorokhobov City Clinical Hospital No. 67, where bilateral hydrothorax, hydropericardium, pneumonitis were detected during the examination. the diagnosis "Postmyocardial syndrome, recurrent course" was established. Hospital treatment was carried out with colchicine, methylprednisolone, acetylsalicylic acid, ticagrelor, losartan, bisoprolol, amlodipine, spironolactone. Against the background of the therapy, the condition improved, the patient began to notice an increase in exercise tolerance, a gradual regression of dull chest pain on the left, body temperature decrease to subfebrile figures. Positive dynamics of laboratory parameters was noted.